Our economic environment : an introduction to the Australian economy part 1 - Gallagher, R. E.; Burkhardt, G. A. (Sydney : Angus and Robertson, 1968)
This report highlights the central position Africa's environment continues to play in sustainable development, as well as its potential to achieve progress in the implementation of the Millennium Development Goals. Profiling Africa's environmental resources as an asset for the continent's development, it also underscores the concept of sustainable livelihoods, and the importance of the environmental initiatives in supporting them.--Publisher's description.
Supplemented by: Workbook to part 1 [by] Frank Oddie. [Rev. i.e., 2d ed. Sydney] Angus and Robertson [1970] vi, 138 p. diagrs., tables. 24 cm.
Includes bibliographical references and index.
aia 18/05/2018
Loans
Keywords: Economics; Economics & economic theory; Australia